Optimasi Waktu dan Kapasitas Produksi Desain Pion Menggunakan Mesin CNC Bubut Melalui Simulasi Autodesk Fusion - Faisal, Bellia Ananda; Leni, Desmarita; Muchlisinalahuddin, Muchlisinalahuddin (Institut Teknologi Adhi Tama Surabaya, 2025)
Modern manufacturing industries face challenges in improving efficiency and product quality. In this study, a pawn was designed using Autodesk Fusion 360, followed by a turning process simulation to optimize machining parameters such as cutting speed, feed rate, and depth of cut. The simulation was conducted to identify potential issues such as tool wear and dimensional inaccuracies before the actual production process. The results showed that implementing simulations effectively minimized production time, improved dimensional accuracy, and reduced tool wear. The applied optimization parameters successfully shortened the production cycle and produced defect-free products that met the required specifications. This study concludes that simulation and optimization in CNC turning machines not only enhance production efficiency and capacity but also ensure consistent product quality, making them highly relevant for modern manufacturing industries.Kata kunci: Simulation, Optimization, CNC Turning